Chinese Herbal Medicine for Primary Liver Cancer Therapy: Perspectives and Challenges - Li, Kexin; Xiao, Kunmin; Zhu, Shijie; Wang, Yong; Wang, Wei (Frontiers in Pharmacology, 2022)
Abstract Primary liver cancer (PLC) is one of the most common solid malignancies. However, PLC drug development has been slow, and first-line treatments are still needed; thus, there is an urgent need to explore and develop alternative strategies for effective PLC treatment. Chinese herbal medicine (CHM) has long been applied clinically due to its advantages of low toxicity and targeting of multiple factors and pathways, and it has great potential for the development of novel natural drugs against PLC. Purpose This review aims to provide an update on the pharmacological mechanisms of Chinese patent medicines (CPMs) and the latest CHM-derived compounds for the treatment of PLC and relevant clinical evaluations. Materials and methods A systematic search of English literature databases, Chinese literature, the Clinical Trials Registry Platform, and Chinese Clinical Trial Registry for studies of CHMs for treatment was performed. Results In this review, we summarize the clinical trials and mechanisms of CPMs for PLC treatment that have entered the clinic with the approval of the Chinese medicine regulatory authority. These included Huaier granules, Ganfule granules, Fufang Banmao capsules, Jinlong capsules, Brucea javanica oil emulsions, and compound kushen injections. We also summarize the latest in vivo and in vitro and clinical studies of CHM-derived compounds against PLC: icaritin and ginsenoside Rg3. Dilemmas facing the development of CHMs, such as drug toxicity and low oral availability, and future developments are also discussed. Conclusions This review deepens the understanding of CHMs as PLC treatments and provides ideas for the development of new natural drugs against PLC.